2006
DOI: 10.1038/sj.tpj.6500359
|View full text |Cite
|
Sign up to set email alerts
|

The role of Gilbert's syndrome and frequent NAT2 slow acetylation polymorphisms in the pharmacokinetics of retigabine

Abstract: Retigabine (RGB) is an investigational antiepileptic drug, which undergoes extensive UGT1A1, 1A9 and 1A4-mediated N-glucuronidation and Nacetylation. The mono-acetylated metabolite of RGB has some pharmacological activity and is denoted AWD21-360. We investigated whether the pharmacokinetics (PK) of RGB and AWD21-360 are altered in subjects with Gilbert's syndrome (GS) and/or with frequent N-acetyltransferase 2 (NAT2) slow acetylator (SA) polymorphisms. Based on consistent genotyping and phenotyping screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Retigabine is metabolized by extensive N-glucuronidation and N-acetylation. However, its clearance seems not to be affected in Gilbert’s syndrome nor by common N-acetyl-transferase type 2 (NAT-2) polymorphisms [35] . A study in Han Chinese people with epilepsy found an association between the effects of SCN1A , ABCC2 and UGT2B7 genetic polymorphisms and oxcarbazepine maintenance doses [36] .…”
Section: Less Robust Evidencementioning
confidence: 99%
“…Retigabine is metabolized by extensive N-glucuronidation and N-acetylation. However, its clearance seems not to be affected in Gilbert’s syndrome nor by common N-acetyl-transferase type 2 (NAT-2) polymorphisms [35] . A study in Han Chinese people with epilepsy found an association between the effects of SCN1A , ABCC2 and UGT2B7 genetic polymorphisms and oxcarbazepine maintenance doses [36] .…”
Section: Less Robust Evidencementioning
confidence: 99%
“…These differences have been attributed to the decline of renal function with age 68. No significant alterations in tolerability and safety were found in subjects with polymorphisms in the UGT1A1 (ie, Gilbert’s syndrome) and/or in N-acetyltransferase, NAT2 (ie, fast or slow acetylator) after a single and multiple (twice daily) 200 mg dose of oral retigabine administered over five days, although the total exposure to the monoacetylated metabolite, AWD21-360, was significantly related to the fast or slow acetylator status of subjects 69. In vitro assays in human liver microsomal preparations showed that 6 μM retigabine (a concentration similar to the peak concentration in subjects receiving a therapeutic dose of the drug) has a moderate capacity to inhibit cytochrome (CYP)2A6 and low or no potential to inhibit CYP1A2, CYP2C8/9/19, CYP2D6, CYP2E1, CYP3A4/5, and CYP4A9/11.…”
Section: Pharmacokinetics Of Retigabine In Humansmentioning
confidence: 96%
“…In a combined pharmacokinetic/pharmacogenomic study in which 36 healthy subjects received oral retigabine 200 mg twice daily for several days, [37] no significant difference in steady-state retigabine exposure was observed between individuals with or without Gilbert's syndrome (i.e. reduced expression of UGT1A1) or between those with slow or rapid N-acetyltransferase 2 acetylator status.…”
Section: Pharmacokinetic Profilementioning
confidence: 97%